2008
DOI: 10.1071/he08152
|View full text |Cite
|
Sign up to set email alerts
|

Framework and tools for planning and evaluating community participation, collaborative partnerships and equity in health promotion

Abstract: Planning and evaluation are regarded as routine in good practice. As health promotion practice and programs are shaped by principles such as partnerships, participation and equity, it is important that we also apply an evaluation lens to these components. Sound planning and evaluation allows practitioners to explain how and why these principles are integrated into their work and what is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Facilitators for effective collaboration and engagement within health promotion initiatives discussed within existing research are also consistent with the facilitators discussed in this article. These include having an environment where work is valued, having trust and effective communication between partners (Delaney, 1994;Dowling, Powell, & Glendinning, 2004;Jolley et al, 2008), being genuine and flexible in collaborative relationships (Gardner, 2005), having a shared vision (Delaney, 1994;Jolley et al, 2008), and understanding the broader context in which the collaboration is taking place (Delaney, 1994).…”
Section: Contextualizing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilitators for effective collaboration and engagement within health promotion initiatives discussed within existing research are also consistent with the facilitators discussed in this article. These include having an environment where work is valued, having trust and effective communication between partners (Delaney, 1994;Dowling, Powell, & Glendinning, 2004;Jolley et al, 2008), being genuine and flexible in collaborative relationships (Gardner, 2005), having a shared vision (Delaney, 1994;Jolley et al, 2008), and understanding the broader context in which the collaboration is taking place (Delaney, 1994).…”
Section: Contextualizing Resultsmentioning
confidence: 99%
“…Such participatory strategies have been found to provide opportunities for discussion of an issue from various perspectives, for increased empowerment, and for innovative solutions to be discovered beyond what an individual person or organization could achieve (Jolley, Lawless, & Hurley, 2008). Furthermore, collaboration has been found to be particularly effective in accomplishing system-wide practice change in complex settings (Reinhardt & Keller, 2009).…”
Section: > Backgroundmentioning
confidence: 99%
“…In partnerships, organizations contribute resources and expertise with the expectation that they can achieve more by working together than if each worked in isolation (Claiborne & Lawson, 2005;Jolley, Lawless, & Hurley, 2008). Because partnerships are complex, changing and contextually derived there is no consensus as to the best way to assess them ( Jolley et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In partnerships, organizations contribute resources and expertise with the expectation that they can achieve more by working together than if each worked in isolation (Claiborne & Lawson, 2005;Jolley, Lawless, & Hurley, 2008). Because partnerships are complex, changing and contextually derived there is no consensus as to the best way to assess them ( Jolley et al, 2008). Three key dimensions are relevant to the TRHP partnership: (a) partners' understandings of the purpose and benefits of partnership, (b) communication and information sharing among partners, and (c) clarity of roles and responsibilities within the partnership (Blue-Banning, Summers, Frankland, & Beegle, 2004;Hosley, Gensheimer, & Yang, 2003;Reback, Cohen, Freese, & Shoptaw, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our reflections are synthesised in a framework derived from other empirical work about what makes for successful researcher-policy actor collaborations. These are: the "four tiers" of linkage and exchange identified by Goering et al (2003), the social processes of knowledge creation and the "communicative perspective" identified by Golden-Biddle et al (2003), the facilitators reported in a systematic review by Innvaer et al (2002 ) of 24 studies, a qualitative study of facilitators and hindrances by Jewell & Bero (2008), a short theoretical review by Locock & Boase (2004), and the principles of partnership evaluation as outlined above including Jolley, Lawless & Hurley (2008). From these we have synthesised six key elements which we found to be crucial to the success of our researcher-policy actor partnership and its output:…”
Section: Methodsmentioning
confidence: 99%